2020
DOI: 10.1136/bmjspcare-2019-002177
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin infusion-related venous pain: prevention by simultaneous intravenous fluids

Abstract: ObjectiveOxaliplatin is a cytotoxic agent frequently used in the treatment of gastrointestinal cancer patients. A known side effect of oxaliplatin administration via a peripheral vein is infusion-related pain. In this retrospective cohort study we compared the incidence of infusion-related pain in patients treated with oxaliplatin with or without simultaneous fluid infusion (FI) (800 mL glucose 5% in 2 hours).MethodsWe retrospectively defined two cohorts: Patients treated with oxaliplatin and simultaneous intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…They found that the incidence of vascular pain in the group simultaneously administered 800 mL of 5% glucose solution was significantly lower than that in the control group (10% vs. 78%; p < 0.0001). 30 This suggests that L-OHP at a lower concentration may have affected vascular pain with the concurrent administration of 5% glucose solution, supporting the results of this study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…They found that the incidence of vascular pain in the group simultaneously administered 800 mL of 5% glucose solution was significantly lower than that in the control group (10% vs. 78%; p < 0.0001). 30 This suggests that L-OHP at a lower concentration may have affected vascular pain with the concurrent administration of 5% glucose solution, supporting the results of this study.…”
Section: Discussionsupporting
confidence: 78%
“…van Ravenstejin et al analysed the effect of co‐administration of 5% glucose solution during L‐OHP administration on the suppression of vascular pain in a retrospective cohort study. They found that the incidence of vascular pain in the group simultaneously administered 800 mL of 5% glucose solution was significantly lower than that in the control group (10% vs. 78%; p < 0.0001) 30 …”
Section: Discussionmentioning
confidence: 96%